High Energy Conversion Efficiency with 3-D Micro-Patterned Photoanode for Enhancement Diffusivity and Modification of Photon Distribution in Dye-Sensitized Solar Cells. Issue 1 (December 2017) - Yun, Min; Sim, Yeon; Cha, Seung; Seo, Seon; Lee, Dong
Abstract Dye sensitize solar cells (DSSCs) have been considered as the promising alternatives silicon based solar cell with their characteristics including high efficiency under weak illumination and insensitive power output to incident angle. Therefore, many researches have been studied to improve the energy conversion efficiency of DSSCs. However the efficiency of DSSCs are still trapped at the around 10%. In this study, micro-scale hexagonal shape patterned photoanode have proposed to modify light distribution of photon. In the patterned electrode, the appearance efficiency have been obtained from 7.1% to 7.8% considered active area and the efficiency of 12.7% have been obtained based on the photoanode area. Enhancing diffusion of electrons and modification of photon distribution utilizing the morphology of the electrode are major factors to improving the performance of patterned electrode. Also, finite element method analyses of photon distributions were conducted to estimate morphological effect that influence on the photon distribution and current density. From our proposed study, it is expecting that patterned electrode is one of the solution to overcome the stagnant efficiency and one of the optimized geometry of electrode to modify photon distribution. Process of inter-patterning in photoanode has been minimized.